Neogene subsidence pattern in the multi-episodic extension systems: Insights from backstripping modelling of the Okinawa Trough. (January 2020) - Fang, Penggao; Ding, Weiwei; Lin, Xiubin; Zhao, Zhongxian; Fang, Yinxia; Li, Chunfeng
Abstract: Extensional systems of back-arc basins have been widely recognized and studied in SE Asia, however the interactions between extensional tectonics and spatial-temporal distributions of tectonic subsidence in an active back-arc basin are poorly known. Using a backstripping technique, we analysed 33 multichannel seismic profiles to calculate the Neogene tectonic subsidence across the entire Okinawa Trough (OT) for the first time. Reconstruction of the tectonic subsidence shows that the OT can be roughly divided into four subsidence stages with variable rate. By comparing the temporal-spatial distribution of the intensive subsidence area, we confirmed that rifting events first occurred in the northern segment (NOT) and middle segment (MOT) from the Miocene to Late Pliocene, and then propagated to the southern segment (SOT) after the Late Pliocene. The factors controlling the rapid tectonic subsidence over the entire OT can be classified into two categories: 1) NE-to NNE-trending normal faulting, related to extension of the OT, and NW- to NWW-trending strike-slip faulting; i.e., the Tokara Fault and the Miyako Fault, related to subduction of the Philippine Sea Plate under the Eurasian Plate; 2) The anomalous rapid subsidence occurred in the southernmost part of the SOT is likely related to the subducted Gagua Ridge which caused magma intrusion resulting from partial melting. We suggest that magmatic bodies produced by partial melting of subducted materials intruded into the crust and created a dense lithosphere, causing this rapid tectonic subsidence. Highlights: The subsidence center first occurred in the NOT and MOT since Miocene, then propagated to the SOT after the Late Pliocene. Rapid tectonic subsidence focuses on the NE-NEE-trending rifting center and the NW-NWW-trending strike slip faults. Anomalous rapid subsidence in the center and southernmost part of the SOT was related with the subduction of Gagua Ridge.